2018
DOI: 10.1177/0049475518800638
|View full text |Cite
|
Sign up to set email alerts
|

Need for guidelines for the combined management of pregnancy and dengue: a retrospective study from an Indian tertiary care maternity hospital

Abstract: The incidence of dengue has risen in India in recent years. Evidence suggests that dengue in pregnancy may be associated with adverse maternal and fetal outcomes. The aim of our study was to analyse outcomes in pregnant women with confirmed dengue infection who had the benefit of close monitoring and intensive management at a tertiary maternity facility. We reviewed hospital data of 44 (0.11%) such women at Fernandez Hospital, a tertiary maternity unit, during the five-year period from 2011 to 2016. Maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…After taking into account titles and abstracts, 852 articles were eliminated, leaving 68 articles for review and potential consideration in this study (Figure 1). Ultimately, 36 articles reporting on 39,632 DENV‐infected pregnant women were included in this meta‐analysis, 6–8,14–46 comprising 18 from Asia (mostly from India, n = 12), 15 from Latin America and 3 from Africa (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…After taking into account titles and abstracts, 852 articles were eliminated, leaving 68 articles for review and potential consideration in this study (Figure 1). Ultimately, 36 articles reporting on 39,632 DENV‐infected pregnant women were included in this meta‐analysis, 6–8,14–46 comprising 18 from Asia (mostly from India, n = 12), 15 from Latin America and 3 from Africa (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike ZIKV causing fetal microcephaly by vertical transmission, preterm delivery, IUGR, or characteristic dengue fever symptoms in newborns are among the most prevalent unfavorable consequences of maternal DENV infection, which are definitely related to higher maternal and fetal morbidity and death. 2 , 3 , 4 In terms of pathogenesis, ZIKV has obvious neurotropism and can directly infect neurons in the fetal brain. However, adverse pregnancy outcomes caused by maternal DENV infection are more relevant to the pathophysiological changes in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of cases of DENV infection during pregnancy have been reported and are definitely associated with increased morbidity and mortality in both mothers and fetuses. 2 , 3 , 4 Meta-analysis showed that preterm birth and low birth weight are the most common adverse pregnancy outcomes associated with maternal DENV infection. 5 , 6 Further histopathological examinations of placentas collected at delivery from maternal DENV infection have shown hypoxic lesions with villous stromal edema and infarcted and preinfarcted areas in 19 of 24 cases, including eight from mothers who did not report overt shock syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 50 years, dengue fever has progressively achieved the status of a pandemic, with approximately 4 billion people at risk of infection, an estimated 390 million cases and 20,000 deaths occurring annually, and both pregnant women and infants belonging to the high-risk group (Messina et al 2015). Nevertheless, few reports exist on DENV vertical transmission, fetal abnormalities, and placental infection (Basurko et al 2009;Ribeiro et al 2013;Nunes et al 2016;Ribeiro et al 2017;Paixao et al 2018a;Kallur et al 2019). Among the most common adverse outcomes of maternal DENV infection are preterm birth, IUGR, and classical dengue fever symptoms in newborns (Basurko et al 2009;Ribeiro et al 2018;Kallur et al 2019), also definitely associated with increased maternal and fetal morbidity and mortality (Kallur et al 2019).…”
Section: Dengue Virus (Denv)mentioning
confidence: 99%